If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(3/7)*x+20 = (6/7)*x-1 // - (6/7)*x-1
(3/7)*x-((6/7)*x)+1+20 = 0
(3/7)*x+(-6/7)*x+1+20 = 0
21-3/7*x = 0 // - 21
-3/7*x = -21 // : -3/7
x = -21/(-3/7)
x = 49
x = 49
| 3(3c-1)-4=5c+5 | | 4x+10-2=40 | | 27-12=3(x-3) | | 2+0.5(0.0625)= | | 2+0.5(0.25)= | | -2.7x-3=2.5x+6 | | -2x-7=2x+25 | | 6n+12/4=40 | | 2x+5x=6(x-9) | | 2+0.5(16)= | | 4-3x=11+4x | | x^2-12x-84= | | X^3-5x^2+16x-30=0 | | X^3-5x^2+16x-30/3=0 | | 12-(2m+3)=2+4m-17 | | X^3-8x^2+37x-50=0 | | X^3-8x^2+37x-50/2=0 | | 7z+6=27 | | 2/3t-8=4 | | X^3-8x^2+37x-50= | | -4=4x+6 | | (6t^2)+19t-36=0 | | -42-(-49)=x/2 | | (c^2)-3c-28=0 | | x+23+2x=0-2x-7 | | c^2-3c-28=0 | | 9x-3(3x-16)=16 | | 5y^3/20x^-4 | | -32-(-37)=x/5 | | (-9)(-5)(2)= | | -2y-y-13=2 | | x-6x+3=13 |